The Effect Of Satisfaction, Trust And Continuance Intention On Mobile Banking User Loyalty - Atika Dwi Andani; Farid Hidayat (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
AbstractPurpose - This study aims to determine whether the satisfaction and trust of Islamic bank customers using mobile banking has an effect on loyalty with continuance intention as a mediating variable.Method - The type of data used in this research is primary data by distributing questionnaires and interviews. The population in this study are Islamic bank customers who use mobile banking in Yogyakarta and for the sampling technique using purposive sampling technique with a total of 100 respondents. The data analysis technique used in this research is with the help of SEM PLS 03.Result - Based on the analysis and discussion results, it shows that there is no market reaction to the announcement of the signing of the BUMN Islamic bank merger on BRIS shares as seen from the abnormal returns before and after the signing of the merger, which there is no significant difference.Implication - Based on the analysis and discussion results, it shows that there is no market reaction to the announcement of the signing of the BUMN Islamic bank merger on BRIS shares as seen from the abnormal returns before and after the signing of the merger, which there is no significant difference.Originality- variables developed to explain the effectThe variables of satisfaction and trust on the loyalty of mobile banking users with continuance intention as a mediating variable have relevance to empirical phenomena. This research has never been done before, especially for Islamic bank mobile banking users in Yogyakarta.